IMPLEMENTATION OF PUBLIC INFORMATION DISCLOSURE POLICY AT THE OFFICE OF THE REPRESENTATIVE FINANCIAL AUDIT BODY OF GORONTALO PROVINCE - Rismayanti, Saprina; Hatu, Rauf A.; Hamim, Udin (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
This research aims to determine and analyze: 1) the implementation of the public information disclosure policy at the BPK Representative Office of Gorontalo Province, studied from four stages, namely: a) initial; b) intermediate; c) advanced; and d) innovative. 2) The factors that determine the implementation of the public information disclosure policy at the Gorontalo Province Representative Office of the BPK are examined from six factors, namely: a) the size and objectives of the policy; b) resources; c) characteristics of implementing agents; d) the attitude or disposition of the implementer; e) communication between organizations; and f) social, economic and political environment.This research approach is qualitative. This type of research is descriptive qualitative. The data collection techniques used were documentation studies, interviews and observations. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research results show that 1) The implementation of the Public Information Openness policy at the BPK Representative Office of Gorontalo Province starting from the Initial, Intermediate and Advance stages has been carried out in accordance with the Open Government Partnership theory but is not yet fully optimal, but the BPK has made innovations to support the implementation of the Public Information Openness policy. 2)The factors that determine the implementation of the Public Information Openness policy at the BPK Representative of Gorontalo Province, namely the Policy Size and Objectives Factor, Resource Factors, and Social, Economic and Political Environmental Factors are supporting and inhibiting factors in the implementation of the policy. Meanwhile, the Characteristic Factor of the Implementing Agent, the Attitude or Disposition Factor of the Implementer, and the Communication Factor between Organizations are supporting factors in the implementation of the Public Information Openness policy at the Gorontalo Province Representative BPK.